THE ROLE OF INTERNATIONAL ORGANIZATIONS IN THE FOREIGN POLITICS OF MODERN UZBEKISTAN - Azamov, Abbos Azam ogli (Educational Research in Universal Sciences, 2023)
This thesis reflects on the role of international economic organizations in foreign economic activities of Uzbekistan. Currently, several international economic organizations carry out their activities through mutual cooperation with states. In particular, Uzbekistan has also been working on membership and cooperation with several international organizations in recent years. For example, the World Trade Organization is an organization that is expected to become a member of Uzbekistan in the near future. We are all aware that Uzbekistan has its positive impact on the growth of both economic and legal potential.